Genomic Characterization of Enterococcus hirae From Beef Cattle Feedlots and Associated Environmental Continuum - Zaidi, Sani-e-Zehra; Zaheer, Rahat; Barbieri, Ruth; Cook, Shaun R.; Hannon, Sherry J.; Booker, Calvin W.; Church, Deirdre; Van Domselaar, Gary; Zovoilis, Athanasios; McAllister, Tim A. (Frontiers in Microbiology, 2022)
Enterococci are commensal bacteria of the gastrointestinal tract of humans, animals and insects. They are also found in soil, water and plant ecosystems. The presence of enterococci in human, animal and environmental settings make these bacteria ideal candidates to study antimicrobial resistance in the One-Health continuum. This study focused on Enterococcus hirae isolates (n= 4601) predominantly isolated from beef production systems including bovine feces (n=4117, 89.5%), catch-basin water (n=306, 66.5%), stockpiled bovine manure (n=24, 0.5%), and natural water sources near feedlots (n=145, 32%), and a few isolates from urban wastewater (n=9, 0.2%) denoted as human-associated environmental samples. Antimicrobial susceptibility profiling of a subset (n=1319) of E. hirae isolates originating from beef production systems (n=1308) showed high resistance to tetracycline (65%) and erythromycin (57%) with 50.4% isolates harbouring multi-drug resistance, whereas urban wastewater isolates (n=9) were resistant to nitrofurantoin (44.5%) and tigecycline (44.5%) followed by linezolid (33.3%). Genes for tetracycline (tetL, M, O , S/M and O/32/O) and macrolide resistance erm(B) were frequently found in beef production isolates. Antimicrobial resistance profiles of E. hirae isolates recovered from different environmental settings appeared to reflect the kind of antimicrobial usage in beef and human sectors. Comparative genomic analysis of E. hirae isolates showed an open pan-genome that consisted of 1427 core genes, 358 soft core genes, 1701 shell genes and 7969 cloud genes. Across species comparative genomic analysis conducted on E. hirae, Enterococcus faecalis and Enterococcus faecium genomes revealed that E. hirae had unique genes associated with vitamin production, cellulose and pectin degradation, traits which may support its adaptation to the bovine digestive tract. E. faecium and E. faecalis more frequently harboured virulence genes associated with biofilm formation, iron transport, and cell adhesion, suggesting niche specificity within these species.